Galgo Español - Alfaro, Karol (My University, 2014)
El tema de este recurso es la locomoción animal del galgo español. Se trata de un interactivo para que el usuario pueda entender cómo se desplaza este animal.

The topic of this resource is the greyhounds locomotion. It consists of an interactive infographic that helps the user understand how this animal moves.
Keywords: Infografía; Interactivo; Galgo español; Locomoción